rationalism, mind cult, cognition, self-cognition, knowledge as the end in itself - Kuzmenko О. (Continuing Professional Education: Theory and Practice, 2019)
The main principles of the antique conception of the cognition such as: the inner value of the cognition and correspondingly knowledge, the focus upon the cognition of the universal categories, the faith in the ideals static nature and invariability of the reality, the priority of the rational cognition of the world are analyzed in the article; it is distinguished that the peculiarity of the antique conception of the self-cognition was the focus on the rational cognition of the universal at a person.